Atypical measles infections in leukaemic children on immunosuppressive treatment. Issue 6025 (26th June 1976) - Pullan, C R; Noble, T C; Scott, D J; Wisniewsk, K; Gardner, P S
Abstract : One case of giant-cell pneumonia and two of encephalopathy, all due to measles infection in children in leukaemic remission on immunosuppressive treatment, were seen recently. The clinical syndromes were variable and atypical and the antibody responses unpredictable. Conventional doses of pooled immunoglobulin failed to protect the two children to whom it was given. Degeneration rather than inflammation seems to characterise the encephalopathy in immunosuppressed children infected with measles virus.